Learning Transformation of Islamic Education Classroom during the Pandemic of COVID-19 - Nofrizal, Nofrizal; Anwar, Khairul; Rambe, Anggi Afina (Khalaqa: Journal of Education and Learning, 2023)
This study aims to identify and analyze the transformation of the Islamic Religious Education (PAI) learning model in elementary schools during the Covid-19 pandemic. This study uses a qualitative method with a case study design. The research locations in Madrasah Ibtidaiyah Negeri 1 and Al Falah Islamic Elementary School. The subjects of this study are PAI teachers and all students. Data collection techniques using interviews, observation, and documentation. Data analysis uses the Matthew B. Milles & Hubberman model which includes data collection, data reduction, data presentation, and drawing conclusions. The results showed that the transformation of the PAI learning model used at the Sulthoniyah Sambas Integrated Islamic Elementary School during the Covid-19 pandemic was blended learning using social media such as Youtube and Whatsapp. PAI learning by using online mode is designed by the School using the Whatsapp Group. Whereas for PAI learning with offline mode, face-to-face meetings take turns, in groups, and the schedule is set.